TELEGRAM-BASED CHATBOT DESIGN FOR ACADEMIC SERVICE AUTOMATION AT FASILKOM UEU USING A LOW-CODE PLATFORM - Gabriela Marry Christiana Simanjuntak; Dewi Setiowati; Binastya Anggara Sekti; Sawali Wahyu (JIKO (Jurnal Informatika dan Komputer), 2026)
Administrative services at the Faculty of Computer Science, Universitas Esa Unggul, face persistent challenges due to high volumes of repetitive inquiries and limited operational hours, which may reduce service efficiency and responsiveness. This study aims to design, implement, and evaluate FasilkomAssist, a 24/7 Telegram-based chatbot developed using the ADDIE framework and a Low-Code/No-Code (LCNC) approach via the n8n workflow automation platform. The system integrates Google Gemini as a Large Language Model (LLM) with Google Sheets, Google Drive, Google Calendar, and Telegram to automate the dissemination of Thesis information and administrative procedures. Evaluation was conducted through Black-box testing, the System Usability Scale (SUS), and User Acceptance Testing (UAT) involving 30 respondents. Results indicate a 96% response accuracy across 17 valid testing scenarios, with an average response time of 4–6 seconds. The SUS score of 70.75 places the system within the “Acceptable” range (Grade C), indicating satisfactory usability with opportunities for optimization. Furthermore, UAT conducted with Faculty Administration Staff yielded a score of 84.67%, confirming functional adequacy and user acceptance. These findings demonstrate that an LCNC-based chatbot can improve efficiency, accessibility, and service quality in academic administrative environments without requiring advanced programming expertise.